Implementation of Role-Based Access Control (RBAC) in a Drug Stock Management Information System - Dea Agustina Purba; Nurmi Hidayasari (Universitas Islam Indragiri, 2026)
Role-Based Access Control (RBAC) is a role-based access management mechanism that restricts user privileges according to their authority within an information system. The implementation of this mechanism is particularly important in pharmacy drug stock management systems, especially at Apotek Pratama dr. Moris, which still relies on manual stock recording. This condition often results in data discrepancies, delays in monitoring expired medications, difficulties in report generation, and the absence of clear access restrictions for each user. This study focuses on developing a web-based drug stock management information system with RBAC as the primary mechanism for user authorization and security. The system was developed using the Waterfall methodology, which includes requirement analysis, system design, implementation, and testing. The application was built using Laravel framework version 11, MySQL database, and the Laravel Spatie Permission package for managing roles and permissions. Black Box Testing results indicate that all functional test scenarios were executed successfully, achieving a 100% success rate. User acceptance testing, conducted using the System Usability Scale (SUS), yielded an average score of 76, categorized as Good. The findings demonstrate that the implementation of RBAC effectively restricts user access based on roles, enhances data security, and improves the accuracy and efficiency of drug stock management compared to the previous manual system.